Determinasi Teknologi dan Tata Kelola Algoritmik dalam Komunikasi Mobile AI: Tinjauan Literatur Sistematis - Velisia Serenada; Maria Risa Puspitasari; Irwansyah . (CV. ITTC INDONESIA, 2026)
This study examines the development, thematic orientation, and theoretical position of research on technological determination in mobile AI-mediated communication systems in the period 2021 to 2026. The review maps publication patterns, methodological tendencies, communication contexts, and emerging theoretical contributions. This study uses a systematic literature review using the PRISMA 2020 framework to synthesize studies on technological determinism in mobile AI communication. Articles were searched in Scopus (2021–2026) using keywords related to determinism, mobile AI, and communication, and filtered for English-language peer-reviewed journals, open access, and social sciences. From an initial 169 articles, a step-by-step selection process resulted in 30 articles as the final analysis corpus. Data from these 30 articles were analyzed using bibliometric mapping (VOSviewer) and narrative synthesis to interpret theoretical positions and deterministic mechanisms in the literature. The findings show that qualitative and conceptual approaches dominate studies on identity, governance, and social communication, while quantitative and modelling approaches are more common in studies of digital economy and infrastructure. Across these themes, mobile AI is positioned not merely as a communication tool but as a computational infrastructure that conditions interaction, visibility, authority, and coordination. Based on this synthesis, the article proposes algorithmic structural determinism as a conceptual lens for understanding how communication processes are shaped by platform infrastructures. Future studies need to specify the operational mechanisms of technological conditioning more clearly and develop more integrative theoretical models.